Nanoarchitectonics of Indocyanine Green/Doxorubicin‐Loaded Hydroxyl Boron Nitride Nanosheets for Chemophotothermal Therapy. Issue 10 (25th October 2022) - Liu, Ming; Sun, Chiyu; Wu, Shuangyan; Zhu, Mingchang; Zhang, Ying
Abstract: Biocompatible hydroxylated boron nitride nanosheets were effectively loaded with indocyanine green and doxorubicin using successive assembly. The indocyanine green/doxorubicin‐loaded hydroxyl boron nitride nanosheets (ICG/DOX@OH‐BNNS) integrated photothermal therapy and chemotherapy into a single nano vehicle. It had been confirmed that ICG/DOX@OH‐BNNS could produce reactive oxygen species and exhibit excellent photothermal effects and light‐triggered faster DOX release with NIR laser irradiation. On the other hand, the fluorescence of DOX in ICG/DOX@OH‐BNNS was also used for visualizing subcellular location. Compared with individual chemotherapy and photothermal therapy, the combined treatment of ICG/DOX@OH‐BNNS could synergistically induce the apoptosis and death of A549 cells and suppress S180 tumor growth in vivo. Abstract : Indocyanine green/doxorubicin‐loaded hydroxyl boron nitride nanosheets (ICG/DOX@OH‐BNNS) could produce ROS and provide an outstanding photothermal effect. Within NIR laser irradiation, IDB also causes a quicker release of DOX. Chemo‐photothermal therapy of ICG/DOX@OH‐BNNS could synergistically trigger the apoptosis and death of A549 cells and inhibit the growth of the S180 tumor in vivo, which has a significant potential for tumor therapy.